2020
DOI: 10.1007/s11764-020-00907-6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the supportive care needs of men and women affected by chemotherapy-induced alopecia? A systematic review

Abstract: To systematically evaluate evidence regarding the unmet supportive care needs of men and women affected by chemotherapy induced alopecia (CIA) to inform clinical practice guidelines. Methods:We performed a review of CINAHL, MEDLINE, PsychINFO, Scopus, the Cochrane Library (CCRT and CDSR) controlled trials databases and clinicaltrials.gov from January 1990 to June 2019 according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) statement. Twenty-seven publications were selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 53 publications
2
27
0
3
Order By: Relevance
“…Quality assessment of the studies was conducted using two quality appraisal tools: one quantitative appraisal tool and one qualitative appraisal tool. This method had previously been used in a similar systematic review [20]. The quantitative appraisal tool consisted of 18 items, evaluated a range of designs including observational study, RCT, nonRCT, cohort, and case study, and classi ed them into the three levels of "good (2)", "fair (1)", and "poor (0)".…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality assessment of the studies was conducted using two quality appraisal tools: one quantitative appraisal tool and one qualitative appraisal tool. This method had previously been used in a similar systematic review [20]. The quantitative appraisal tool consisted of 18 items, evaluated a range of designs including observational study, RCT, nonRCT, cohort, and case study, and classi ed them into the three levels of "good (2)", "fair (1)", and "poor (0)".…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The framework provides a tool for cancer care professionals and program managers, allowing them to design services based on the type of assistance that cancer patients may need [19]. Based on the current literature, individual supportive care needs are classi ed into eleven aspects of supportive care needs, including psychosocial/emotional, physical, health system/information, family-related, social, interpersonal/intimacy, practical, daily living activity, spiritual/existential, patient-health professional communication, and cognitive needs [20,21]. The current trend in modern medicine is changing from a disease-based model to a patient-centered model in which patients are active and patients' preferences and care needs are considered [22].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals and researchers have a growing awareness of the importance to identify gaps in supportive care experiences for people affected by cancer. Though the timely identification of unmet needs, planning and delivery of cancer services can be targeted to improve patients' overall health-related quality of life and recovery [7]. To date, a growing number of systematic reviews have examined the unmet needs in various cancer populations such as prostate [8], bladder [9], gynaecological [10], kidney [11], penile [12], breast [13], and colorectal [14], including older populations affected by cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…These young men may have enduring physical and psychological needs related to diagnosis and treatments comparative to their youth. Existing studies have reported enduring and longlasting effects from treatment which include problems related to infertility, altered neurological and respiratory function, problems in securing life insurance and employment, psychological distress (such as fear of cancer recurrence), altered masculinity/ body image, concerns related to chemotherapy-induced alopecia, and challenges with intimacy and relationships [6,7,15,16,19]. Physical needs are prevalent in testicular cancer survivors, who on average may experience 4.5 physical symptoms (SD = 4.4; range, 1-28) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although both men and women cope with hair loss caused by diseases and medical treatments, relatively little scholarly attention has been given to men's experiences of hair loss [1][2][3][4]. This may be due to the assumption that hair loss is more of a problem for women [2,5], who place more importance on their appearance than men [5,6] and for whom hair represents a significant aspect of their identity [7,8] and is perceived as a major indicator of reproductive potential, femininity, sexuality, and attractiveness in society [7,9,10].…”
Section: Introductionmentioning
confidence: 99%